A cyclic peptide antenna ligand for enhancing terbium luminescence. Issue 11 (29th April 2021) - Ji, Fei; Shao, Shiqun; Li, Zhonghan; Wang, Siwen; Chaudhuri, Rohit; Guo, Zhili; Perkins, Nicole G.; Sarkar, Priyanka; Xue, Min
Abstract : We present here a cyclic peptide ligand, cy(WQETR), that binds to the terbium ion (Tb 3+ ) and enhances Tb 3+ luminescence intensity through the antenna effect. Abstract : We present here a cyclic peptide ligand, cy(WQETR), that binds to the terbium ion (Tb 3+ ) and enhances Tb 3+ luminescence intensity through the antenna effect. This peptide was identified through screening a cyclic peptide library against Tb 3+ with an apparent EC50 of 540 μM. The tryptophan residue from the peptide directly interacts with the Tb 3+ ion, which provides access to a low-lying triplet excited state of the tryptophan. Direct excitation of this triplet state enables energy transfer to the Tb 3+ ion and enhances Tb 3+ luminescence intensity by 150 fold. We further showcase the application of this cy(WQETR)–Tb 3+ system by demonstrating the detection of tromethamine with a detection limit of 0.5 mM.